Research on Artificial Post-Treatment Technology of FDM Forming Parts. (October 2019) - Liu, Jinjin; Gu, Hai; Li, Bin; Zhu, Lu; Jiang, Jie; Zhang, Jie
Abstract: 3D printing technology is a high and new technology gradually developed from the mid-1980s, leading the manufacturing technology of the third revolution. The 3D printing process includes modeling, data processing, selective process printing and post-processing. FDM technology is the most widely used technology at present, but the molding accuracy is not high. Due to the "step effect", the printed parts have rough surface, obvious stripes, poor surface quality, and cannot meet the customer's or specified requirements, so post-processing is very important. This paper mainly studies and summarizes the manual post-processing technology of FDM printed parts, and provides the specific implementation method of post-processing, providing reference for the post-processing of FDM formed parts and other forming processes.